Sociedade, memória e mulheres Society, memory and women - Lunz, Leandro da Silva; Nader, Maria Beatriz (Revista Vozes dos Vales: Publicações Acadêmicas, 2023)
The development of social relations in the course of history was strongly characterized by the use of memory as an instrument of power, acting for a social construction marked by class differences and restricting the expected behaviors of the actors involved in this complex "relational game." Domestic care, motherhood, and child education were historically recognized as feminine spaces par excellence, and it was up to the woman to make the private space the locus of feminine potential exercise. To the man was assigned the role in of the public world as a social function, a space destined for business, intellectuality, and visibility. A man plays the roles of provider, husband, and father, emphasizing his superiority over those under his control by his subjection. The construction of this political order, supported by the construction of essentially differentiated female and male social roles, allowed the predominance of male interests in the various social fields. To discuss this theme, Jacques Le Goff (1990), Michelle Perrot (2005) and e Losandro Tedeschi (2014) were used as main references
Keywords: Visibility; Memory Use; Social Construction